The Great Recession and Job Loss Spillovers : Impact of Tradable Employment Shocks on Supporting Services - Nguyen, Ha (World Bank, Washington, DC, 2016)
This paper explores the spillover effects of job losses via input-output linkages during the Great Recession. Exploiting exogenous variation in tradable employment shocks across U.S. counties, the paper finds that job losses in a county’s tradable sectors cause further job losses in the county’s supporting services. For a given county, a 10 percent exogenous decline in tradable employment reduces supporting industries’ employment by 3.8 percent. In addition, a county’s regional supporting services are relatively less affected by its tradable job losses than its local supporting services are, which reinforces the argument that the spillovers are due to input-output linkages.